1987
DOI: 10.1093/schbul/13.4.727
|View full text |Cite
|
Sign up to set email alerts
|

Living With the Mentally Ill: Factors Affecting Household Complaints

Abstract: Data provided by case managers in community support programs are used to analyze the problems of families providing shelter to mentally ill relatives. Factors affecting complaints in 345 family households are contrasted with factors leading to complaints in a subsample of 622 other residential alternatives. Behavioral problems are the best predictors of complaints from all households regardless of type, but some causal factors identified are unique to family residences, notably failure to perform household cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 23 publications
1
18
0
3
Order By: Relevance
“…Positive symptoms are probably implicated in disruptive phenomena in the family environment. There is also evidence from other studies that positive symptoms have an important role in the perceived burden (Grad & Sainsbury 1963, Gubman et al 1987).…”
Section: Discussionmentioning
confidence: 90%
“…Positive symptoms are probably implicated in disruptive phenomena in the family environment. There is also evidence from other studies that positive symptoms have an important role in the perceived burden (Grad & Sainsbury 1963, Gubman et al 1987).…”
Section: Discussionmentioning
confidence: 90%
“…In addition to depression, delusions, and hallucinations, AD patients often develop disruptive behaviors. The term 'disruptive' refers to behaviors that are reported by relatives of AD patients to violate household or societal rules (Gubman et al, 1987). Neuropsychiatric and other behavioral disturbances are important in the diagnosis, prognosis and management of AD.…”
Section: Introductionmentioning
confidence: 99%
“…1988). Dealing with a person affected by a serious illness whose behaviour may at times be difficult and unpredictable makes considerable demands on the main caregiver at home (Guarnaccia & Parra 1996; Gubman et al 1987; Stueve et al. 1997).…”
Section: Caregivers Coping In Familiesmentioning
confidence: 99%
“…Research carried out in the 1950s identified families as being responsible for their members’ mental illness (Guarnaccia & Parra 1996). The family’s interactions and communication patterns were cited as one of the main causes for the development of mental illness (Gubman et al. 1987).…”
Section: Introductionmentioning
confidence: 99%